2019
DOI: 10.9734/ibrr/2019/v10i130113
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Impact of Some Selected Plants on Haematological Parameters of Testosterone and Estradiol Induced Benign Prostatic Hyperplasia Adult Male Rats

Abstract: Background: Benign prostate hyperplasia (BPH) is an age-related disease of unknown etiology, characterized by prostate enlargement. The effect of Prosopis africana (PA), Vernonia amydalina (VA) and Ocimum gratissmum (OG), plant extracts on haematological parameters of BPH animal model was investigated. Methods: BPH was induced in 45 male Wistar rats (250-350 g) by exogenous injection of testosterone and estradiol in staggered doses for 3 weeks. To confirm BPH induction, some animals were sacrificed; hist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 57 publications
1
1
0
Order By: Relevance
“…Significantly increased WBC count in the BPH control aligns with prior studies and is attributable to increased immune and phagocytic response due to high levels of ROS cum free radicals caused by BPH induction (Ugwu et al, 2019). Increased free radicals trigger an immune response resulting in increased synthesis and recruitment of WBCs to impede further spread and clear existing radicals (Ijioma et al, 2019).…”
Section: Effects Of Cesh On Haematological Indices Of Bph-induced Ratssupporting
confidence: 80%
See 1 more Smart Citation
“…Significantly increased WBC count in the BPH control aligns with prior studies and is attributable to increased immune and phagocytic response due to high levels of ROS cum free radicals caused by BPH induction (Ugwu et al, 2019). Increased free radicals trigger an immune response resulting in increased synthesis and recruitment of WBCs to impede further spread and clear existing radicals (Ijioma et al, 2019).…”
Section: Effects Of Cesh On Haematological Indices Of Bph-induced Ratssupporting
confidence: 80%
“…Furthermore, no detectable levels of basophils and monocytes in the normal control rats, BPH control, finasteride, and graded doses of CESH treated BPH induced rats. These findings showed that BPH did not affect the neutrophil, lymphocytes, and eosinophil counts, contrary to Ugwu et al (2019).…”
Section: Effects Of Cesh On Differential White Blood Cell Counts Of B...mentioning
confidence: 72%